2020
DOI: 10.18203/2394-6040.ijcmph20200434
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on ante-natal depression in a tertiary health care hospital in Navi Mumbai

Abstract: Background: Depression is a common source of disability among women. Antenatal depression has been often overlooked and under diagnosed, throughout the world especially in the developing countries like India. This study was conducted to assess the mental health status of pregnant women attending the antenatal clinic in a tertiary health care hospital.Methods: A cross-sectional study was conducted over a period of three months among randomly selected pregnant women attending the antenatal clinic of a tertiary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The incidence of depression and unfavorable pregnancy outcomes may be reduced by early identification of probable depression in pregnant women. Prenatal depression should be screened for, diagnosed as part of routine pregnancy care, and treated promptly to protect the health and safety of expectant mothers [ 13 ]. If it is not treated and recognized promptly, it could develop into postpartum depression [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of depression and unfavorable pregnancy outcomes may be reduced by early identification of probable depression in pregnant women. Prenatal depression should be screened for, diagnosed as part of routine pregnancy care, and treated promptly to protect the health and safety of expectant mothers [ 13 ]. If it is not treated and recognized promptly, it could develop into postpartum depression [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews conducted in low-and middle-income countries reported the prevalence of antenatal depression ranging between 19.2% and 34% with variation in sociodemographic, obstetric, and measurement factors [4,5,7,8]. Previous studies in India have reported a wide-ranging prevalence of antenatal depression between 8.7% and 65% [9][10][11][12][13], with variation according to the type of screening tool and study setting. Subsequently, another systematic review in India reported that the prevalence of prenatal depression ranged from 9.18% to 65.0% in Northern, Western, and Southern India [14].…”
Section: Introductionmentioning
confidence: 99%